Strategi Komunikasi Pemasaran PT. Rumah Daun Kreatif untuk Mempertahankan Produk Lokal Kain Jumputan di Kota Palembang - Karisa Dwi Heria Rosa; Isna Wijayani (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to determine the marketing communication strategy of PT Rumah Daun Kreatif in maintaining local tie-dye textile products in Palembang City amidst increasingly competitive creative industry conditions. The study employed a qualitative method with a case study approach, collecting data through in-depth interviews, observations, and documentation studies of internal company personnel. The results indicate that PT Rumah Daun Kreatif implements integrated marketing communications by utilizing social media such as Instagram and mass media such as television, as well as participation in various events as promotional tools. The promotional strategy focuses on strengthening brand awareness by highlighting local cultural values, unique traditional motifs, and the manual manufacturing process as key attractions. The use of storytelling through digital media is also effective in building emotional closeness and consumer loyalty. The study concludes that an integrated and consistent marketing communication strategy is key to PT Rumah Daun Kreatif's success in maintaining the existence of local tie-dye textile products in both local and national markets.